Clinical Significance of Incidentally Detected Torus Tubarius Calcification. Issue 5 (September 2017) - Buch, Karen; Nadgir, Rohini N.; Qureshi, Muhammad Mustafa; Ozonoff, Al; Sakai, Osamu
Abstract : Objectives: Calcification of the torus tubarius has been rarely reported in the literature. Histopathologic studies have previously described cases of Eustachian tube calcification and cite an association with increasing patient age. The purpose of this study was to examine the prevalence of torus tubarius calcification and potential clinical significance on an unrestricted patient population using thin-section computed tomography (CT), which has not been previously reported. Methods: After the institutional review board approval, 1571 consecutive patients who underwent noncontrast head CT between January 2011 and July 2011 were retrospectively reviewed for torus tubarius calcification. Images were acquired at 1.25-mm slice thickness using a 64-detector row CT. Medical records were reviewed for chronic medical conditions including chronic kidney disease, alcoholism, autoimmune conditions, endocrine disorders, elevated alkaline phosphatase levels, history of otitis media, purified protein derivative positivity, history of head and neck surgery and radiation, and human immunodeficiency virus infection. Motion-limited studies and patients with limited clinical data were excluded. Statistical analyses were performed using the independent sample t test and Fisher exact test. Results: Ten (0.6%) of 1571 patients had torus tubarius calcification, of which 7 (70%) were unilateral, and 3 (30%) were bilateral calcification. There was no significant association between torus tubarius calcification and common medical disorders including endocrine disorders, human immunodeficiency virus, chronic kidney disease, alcoholism, purified protein derivative positivity, history of head and neck surgery or radiation, and autoimmune diseases. Conclusions: Based on the largest series to date on an unrestricted population using thin-section CT imaging, calcification of the torus tubarius is a rare entity with an overall prevalence of 0.6%. Although the clinical significance remains uncertain, there is no significant association between torus tubarius calcification and common medical conditions.